Social Interaction of Generation Z in China - Hu, Sumei (Science Insights, 2025)
Due to the advancement of mutual information technology and the impacts of globalization and cultural pluralism, Generation Z has developed notions of social life and social channels that are significantly different from those of the preceding generations. A thorough understanding of its peculiarities is conducive to our in-depth knowledge of this group. This article is a discussion of populous forms of social interaction among Generation Zers in China, such as Dazi social interaction, circle-based social interaction, and social media-based interaction. These forms of social life are the result of technological development and the advancement of urbanization, emblematic of the emotional needs of Chinese youth and their individual expression. The study also finds that these novel social interactions bring challenges to this generation, such as communication apprehension, information cocoons, cyber violence, and privacy breaches.